Ensinar Educação Física: a beleza de um caminho indefinido - Beatriz Manuela Oliveira Baptista (2020)
The professional internship incorporates in itself a large part of a final and fundamental stage of my training and the purpose of this report is to explain my evolution, growth and all the pedagogical experience as a physical education teacher, throughout the academic year 2019/2020 . The professional internship took place at Agrupamento de Escolas de Rio Tinto Nº3 (Escola Secundário de Rio Tinto e Escola Básica Frei Manuel de Santa Inês) in the council of Gondomar, with the internship group consisting of three student-interns. The entire process was accompanied by the school's cooperating professor and the faculty's advisor. This report is structured in five main chapters. The first is an introduction where I make a brief general reference about the theme of this work. In the second chapter, I convey what my initial expectations were as a student and future teacher, taking into account the knowledge and experiences that i acquired over the course of my academic career. There is also a personal and institutional contextualization where i try to discover who I am in the now and who I intend to be in the after. In the third chapter, I explore the interaction between all stakeholders (school, teacher, students and society), as well as the characterization of the classes I taught). The fourth chapter reflects the whole process that I went through during this peculiar academic year and the options related to teaching that I took during the professional internship. A study project is also presented aiming to develop social the skills of the class. In that same chapter, my participation in school and relations with the community is exposed, culminating in a deep reflection about my professional development. Finally, the fifth chapter is the conclusion where I make a reflection about the importance that the professional internship had in my integral professional and personal growth in the search to become an excellent physical education teacher.